Sizing solar-assisted natural rubber dryers - Pratoto, A; Daguenet, M; Zeghmati, B (Solar energy, 1997)
Due to the lack of firewood, the use of solar energy in drying of natural rubber has been envisaged and it has been the subject of several works. The present work is concerned with the design of solar-assisted natural rubber dryers. The system performance is estimated using the average day method. The possibility of heat dumping and the configuration of the collector array are taken into account. To facilitate the user in making a rapid estimation on the collector area required, a simplified sizing method is developed. To this end, an empirical relation is performed by correlating the results of short-cut simulation to design parameters which are easily determined.